Managers’ Views on Dividend Policy of Nepalese Enterprises - Adhikari, Nabaraj (NRB Economic Review, 2014)
This paper analyses the perceptions of managers on dividend policy by surveying the views of 125 Managers of 66 companies listed at Nepal Stock Exchange. This survey is motivated by the observation that much of dividend policy theory is implicitly based on a capital market perspective. Out of 66 listed enterprises surveyed, 16 were from banks and 50 were from nonbanks. To examine whether views of managers on dividend policy differ between banking group and non-banking group, chi-square analysis was used. Spearman’s rank correlation coefficient was calculated to find out the degree of relationship between the responses of banking group and non-banking group and it was tested for significance at 5 percent level of significance. Median value of responses for each statement of observation on dividend policy was computed to highlight the significance of observation. The results of this study indicate that the most important determinants of dividend policy in order are growth rate of enterprise’s earnings, patterns of past dividends, availability of investment opportunities; managers have more emphasis on the stable dividend policy; and dividend policy influences the value of the enterprise in Nepal. The findings of the study could be useful for research scholars, and users of financial information including corporate managers, investors, financial analysts, and regulators. The current study extends limited previous research based on questionnaire and survey related dividend policy. It thus provides new evidence from a pre-emerging capital market of Nepal.